Factors Influence on Job Satisfaction of EFL Students in a Public University in Battambang Province - Seavmey, Rin; Narin, Seng; Sreylin, Tep; Kinlann, Sorn (Journal of English for Specific Purposes in Indonesia, 2025)
This research study investigates the factors that influence the job satisfaction of English as a Foreign Language (EFL) college students. Job satisfaction is a critical aspect of career development and overall well-being, particularly for students aspiring to enter the field of English language teaching. The study employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather data on various factors such as work environment, professional development opportunities, salary and benefits, and interpersonal relationships. Findings from the study reveal that factors such as supportive work environments, opportunities for professional growth, and fair compensation significantly impact the job satisfaction of EFL college students. Additionally, the qualitative data provides deeper insights into the emotional and psychological aspects of job satisfaction, shedding light on the importance of intrinsic motivation and a sense of purpose in one's career. The results of this study have implications for educational institutions, language teaching programs, and career counselors in understanding and addressing the needs of EFL college students as they prepare to enter the workforce.